Study on Stability of Super-high Straight-web Cellular Steel Sheet Pile Cofferdam. Issue 5 (September 2019) - Deng, Yang; He, Changhai; Fu, Shaojun; Wu, Xiguo; Yang, Ruiting
Abstract: In recent years, steel sheet pile cofferdam has been adopted in some hydropower reconstruction and extension projects because of its many advantages. However, due to insufficient understanding of the bearing mechanism of super-high cellular cofferdam and lack of Engineering experience, there is no exact method to accurately predict the deformation and failure forms of the cofferdam, and there is no perfect safety and economic design theory, which restricts its popularization and application. Taking the Tarbela 4th Extension Project as background, the mechanical behavior and stability evaluation of the cofferdam in 30m deep water during construction and operation are studied by FEM, and influence of structural form and parameters on deformation characteristics of key parts is analysed. Results show that the maximum interlock tension occurs near mudline or top of berm during high lateral load. Development distribution of shear deformation are more in line with the Kitajima Shoichi' method. The overturning deformation of cell can be effectively restrained by embedment, the rotation point changes regularly with the increase of berm and embedment. The sliding surface in cell conforms to Hansen's calculation theory, the position of rotation and change of base pressure are closer to the Japanese standard. With the stiffness loss, the change of interlock tension is similar to the damage of low carbon steel, the shear sliding surface is related to berm which above the top overturning deformation is the largest. Based on the stability of cofferdam, there are various combinations of berm height and embedded depth, which can reduce the quantity of embankment works and the cost of later maintenance. The research results are of reference significance for the design and construction of similar super-high steel sheet pile cofferdams.